Interferon-Gamma (IFN-γ) is Elevated in Wound Exudate from Hidradenitis Suppurativa - Banerjee, Anirban (Immunol Invest, 2016)
Hidradenitis suppurativa (HS) is a chronic recurrent inflammatory disease of apocrine glands which affects 1% to 4% of young adults. The purpose of this study was to investigate inflammatory cytokines in effluent from HS lesions and to identify potential local drivers of inflammation in HS. Wound fluid specimens from HS patients (n=8) and age-matched chronic wound patients (n=8) were selected for analysis. The Hidradenitis Suppurativa Score (HSS) was used to determine extent of HS activity. Cytokine analysis was conducted using Meso Scale Discovery cytokine and proinflammatory panels. Interferon-gamma (IFN-γ) was significantly elevated in the HS effluent compared to chronic wounds (1418 ± 1501 pg/ml compared to 102.5 ± 138 pg/ml, p 0.027). HS effluent also had significantly higher levels of TNF-β (9.24 ± 7.22 pg/ml compared to 1.65 ± 2.14 pg/ml, p 0.03). There was no significant difference in any other cytokines. There was no significant difference in demographics in the HS compared to chronic wound cohorts. Mean HSS in the HS cohort was 68.88 (SD ± 41.45). In this proof of concept pilot study, IFN- γ was significantly elevated in HS effluent. TNF-β/LT-α levels were also elevated in HS, although the levels were more modest. Further studies should focus on molecular drivers of tissue injury in HS, and the relationship between HS effluent cytokine profile and disease activity.